2008
DOI: 10.1051/0004-6361:200809572
|View full text |Cite
|
Sign up to set email alerts
|

The long-term X-ray variability properties of AGNs in the Lockman Hole region

Abstract: Context. We present the results from a detailed X-ray variability analysis of 66 AGN in the Lockman Hole, which have optical spectroscopic identifications. Aims. We compare, quantitatively, their variability properties with the properties of local AGN, and we study the "variabilityluminosity" relation as a function of redshift, and the "variability -redshift" relation in two luminosity bins. Methods. We use archival data from the last 10 XMM-Newton observations of the Lockman Hole field to extract light curves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 25 publications
11
58
2
Order By: Relevance
“…Similar values are found also for higher redshift QSOs, e.g. by Manners et al (2002), up to z = 2 (k = 0.27, still for time scales of days), and by Papadakis et al (2008), up to z ∼ 3.4 (k = 0.33, for time scales of tens of days). Stronger dependences are instead found by Paolillo et al (2004) (k ∼ 0.65, in the redshift range 0.5 < z < 1.3) and by Almaini et al (2000) (k = 0.75, for z < 0.5).…”
Section: Dependence On X-ray Luminosity and Redshiftsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar values are found also for higher redshift QSOs, e.g. by Manners et al (2002), up to z = 2 (k = 0.27, still for time scales of days), and by Papadakis et al (2008), up to z ∼ 3.4 (k = 0.33, for time scales of tens of days). Stronger dependences are instead found by Paolillo et al (2004) (k ∼ 0.65, in the redshift range 0.5 < z < 1.3) and by Almaini et al (2000) (k = 0.75, for z < 0.5).…”
Section: Dependence On X-ray Luminosity and Redshiftsupporting
confidence: 84%
“…Manners et al (2002) also reported tentative evidence of a stronger variability for sources at z > 2. Finally, Papadakis et al (2008) compared the variability of highredshift AGNs in the Lockman Hole region with that of nearby AGNs by Markowitz & Edelson (2004), finding evidence of an increase with redshift. Owing to the strong correlation of sources in the L X -z plane (Fig.…”
Section: Dependence On X-ray Luminosity and Redshiftmentioning
confidence: 99%
“…It is generally believed that variable X-ray irradiation can drive optical variations by means of variable heating of the internal parts of the disk on relatively short timescales, days to weeks, while intrinsic disk instabilities in the outer parts of the disk dominate on longer timescales, months to years, propagating inwards and modulating X-ray variations in terms of Compton up-scattering in the corona (Czerny 2004;Arévalo 2006Arévalo , 2009Papadakis et al 2008;McHardy 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Almaini et al (2000) and Manners et al (2002) have used ROSAT data to study the variability properties of 86 and 156 AGN, respectively. Both Paolillo et al (2004) and Papadakis et al (2008), thanks to the study of variability of Chandra and XMM-Newton deep field observations, trace a higher redshift AGN population. Paolillo et al (2004) study a sample of 430 Chandra sources from the deep field south (74 of which result to be variable) and Papadakis et al (2008) 66 AGN from the XMM-Newton Lockman Hole observations.…”
Section: Correlations Between the Excess Variancementioning
confidence: 99%
“…Both Paolillo et al (2004) and Papadakis et al (2008), thanks to the study of variability of Chandra and XMM-Newton deep field observations, trace a higher redshift AGN population. Paolillo et al (2004) study a sample of 430 Chandra sources from the deep field south (74 of which result to be variable) and Papadakis et al (2008) 66 AGN from the XMM-Newton Lockman Hole observations. Both these works study AGN variability, but only on time scales longer than ∼1 day.…”
Section: Correlations Between the Excess Variancementioning
confidence: 99%